Política e direito na mobilidade urbana do município de Santos - Guimarães, Leonardo Bernardes (2016)
This paper is to comment two aspects of urban mobility in the city of Santos, the law and policy that surround it. Considering that the law does not treat conceptually satisfactorily about politics and public policies surrounding the issue, rescues initially from another branch, that¿s the subject of political science as a way of translating PNMU. Regardless of this fact, and the intrinsic relationship between law and politics, here is considered thoughts and concepts or even thought systems proposed by law. This paper intends to comment how closer the theory of reality is close to the reader, always suggesting solutions that have win-win situations and enable the sustainable development of the city in view of the relevance of the topic to the healthy quality of life of citizens who studies, works and performs their daily activities within this beautiful city. In addition, this paper presents data, surveys and strategies contained in public documents as a way of basing the brought solutions. This paper also seeks to demonstrate impartiality strengths and weaknesses of the mobility policy, not demonstrating party-political or personal preferences that regards to policy and politics choices of the municipality.